Causes of floods and flood protection in Subcarpathia - Szuhányi, György (Acta Agraria Debreceniensis, 2006)
Subcarpathia is one of the richest regions in surface waters in the Ukraine. Due to its geographical, relief and climatic conditions, it belongs to the active precipitation zone, where great floods frequently occur. As a result of many years of observation, it can be concluded that the interactions of many natural factors can lead to various floods in the catchment area of the river Tisza. These are mostly hydro-meteorological factors, which can lead to great floods with the characteristics of the formed flow. Human activity also significantly influences the occurance of floods: clearing, which can accelerate the process of the runoff, ploughing in the catchment area, which can lead to erosion and the utilisation of areas endangered by floods for various economic sectors.A series of questions arose in recent years regarding the formation of floods: what could be the causes of floods and what actions need to be made to prevent them. The evaluation of floods made us conclude that passive protection by using dams does not always ensure protection against floods as these were constructed in different times for different water levels. Many factors can affect the whole process which cannot be foreseen, therefore the development of new solutions and new technologies is necessary in flood protection.